Regularized brownian motion on the Siegel disk of infinite dimension - Airault, H.; Malliavin, P. (Український математичний журнал, 2000)
We construct a process of Brownian motion on the Siegel disk of infinite dimension. Побудовано процес броунівського руху на нескінченновимірному диску Сігела.